Enhancing Maritime Safety Standards through Advanced Technologies and Professional Education - Wulandari, Retno Sawitri; Larsen Barasa; Marihot Simanjuntak; Mudakir; Rosna Yuherlina Siahaan (TEMATIK, 2024)
This research explores the integration of advanced technologies, such as machine learning and sensor data analysis, into maritime education to enhance safety standards. The study focuses on cadets' knowledge, attitudes, and perceptions of safety practices and examines incident data to predict and prevent maritime incidents. Findings reveal that while cadets have substantial knowledge of safety regulations, their attitudes towards safety culture need reinforcement. The alignment of education programs with industry requirements and adherence to international standards are emphasized. Additionally, the integration of technology into curricula is crucial for preparing future maritime professionals. The research underscores the need for a comprehensive approach combining technical knowledge, professional attitudes, and advanced technology to significantly improve safety standards and ensure the sustainability of the maritime industry.